Complementary dynamic BH3 profiles predict co-operativity between the multi-kinase inhibitor TG02 and the BH3 mimetic ABT-199 in acute myeloid leukaemia cells - Pallis, Monica; Burrows, Francis; Ryan, Jeremy; Grundy, Martin; Seedhouse, Claire; Abdul-Aziz, Amina; Montero, Joan; Letai, Anthony; Russell, Nigel (Impact Journals, 2016)
Direct co-operation between sensitiser molecules BAD and NOXA in mediating apoptosis suggests that therapeutic agents which sensitise to BAD may complement agents which sensitise to NOXA. Dynamic BH3 profiling is a novel methodology that we have applied to the measurement of complementarity between sensitiser BH3 peptide mimetics and therapeutic agents. Using dynamic BH3 profiling, we show that the agent TG02, which downregulates MCL-1, sensitises to the BCL-2-inhibitory BAD-BH3 peptide, whereas the BCL-2 antagonist ABT-199 sensitises to MCL-1 inhibitory NOXA-BH3 peptide in acute myeloid leukaemia (AML) cells. At the concentrations used, the peptides did not trigger mitochondrial outer membrane permeabilisation in their own right, but primed cells to release Cytochrome C in the presence of an appropriate trigger of a complementary pathway. In KG-1a cells TG02 and ABT-199 synergised to induce apoptosis. In heterogeneous AML patient samples we noted a range of sensitivities to the two agents. Although some individual samples markedly favoured one agent or the other, in the group as a whole the combination of TG02 + ABT-199 was significantly more cytotoxic than either agent individually. We conclude that dynamic NOXA and BAD BH3 profiling is a sensitive methodology for investigating molecular pathways of drug action and complementary mechanisms of chemoresponsiveness.